Ischemic preconditioning increases muscle perfusion, oxygen uptake, and force in strength-trained athletes - Paradis-Deschênes, P.; Joanisse, D. R.; Billaut, F. (Applied Physiology, Nutrition, and Metabolism, 2016)
Muscle ischemia and reperfusion induced by ischemic preconditioning (IPC) can improve performance in various activities. However, the underlying mechanisms are still poorly understood. The purpose of this study was to examine the effects of IPC on muscle hemodynamics and oxygen (O2) uptake during repeated maximal contractions. In a cross-over, randomized, single-blind study, 10 strength-trained men performed 5 sets of 5 maximal voluntary knee extensions of the right leg on an isokinetic dynamometer, preceded by either IPC of the right lower limb (3×5-min compression/5-min reperfusion cycles at 200 mm Hg) or sham (20 mm Hg). Changes in deoxyhemoglobin, expressed as a percentage of arterial occlusion, and total hemoglobin ([THb]) concentrations of the vastus lateralis muscle were monitored continuously by near-infrared spectroscopy. Differences between IPC and sham were analyzed using Cohen`s effect size (ES) ± 90% confidence limits, and magnitude-based inferences. Compared with sham, IPC likely increased muscle blood volume at rest (increase [THb], 46.5%; ES, 0.56; 90% confidence limits for ES, -0.21, 1.32). During exercise, peak force was almost certainly higher (11.8%; ES, 0.37; 0.27, 0.47), average force was very likely higher (12.6%; ES, 0.47; 0.29, 0.66), and average muscle O2 uptake was possibly increased (15.8%; ES, 0.36; -0.07, 0.79) after IPC. In the recovery periods between contractions, IPC also increased blood volume after sets 1 (23.6%; ES, 0.30; -0.05, 0.65) and 5 (25.1%; ES, 0.32; 0.09, 0.55). Three cycles of IPC immediately increased muscle perfusion and O2 uptake, conducive to higher repeated force capacity in strength-trained athletes. This maneuver therefore appears relevant to enhancing exercise training stimulus.